Application of magnetic field for reduction of sludge bulking in activated sludge system - Zaidi, Nur Syamimi (2016)
Activated sludge treatment process is the most commonly used technology in treating municipal wastewater. Nevertheless, its stable operation is always plagued by occurrence of sludge bulking. Existing control approaches have led to various drawbacks and caused more problematic issues in the treatment system. Therefore, this study investigated the use of magnetic field on activated sludge in controlling the occurrence of sludge bulking and to further enhance wastewater treatment process. The initial stage of the study involved batch tests where statistical experimental design was implemented. Factorial design was carried out first, followed by central composite design experiment. The studies showed that turbidity reduction, aggregation and settling velocity of the activated sludge were affected by factors of magnetic field, exposure time, biomass concentration and mixing intensity. Interaction effects between the factors were also observed. Statistical models describing relationship between the variables were developed. From the study, the highest turbidity reduction (89.1%), aggregation (97.8%) and settling velocity (0.68 cm/min) were achieved under optimal condition of 88.0 mT magnetic field, 16.5 hrs exposure time, 2800 mg/L biomass concentration and 300 rpm mixing intensity. The following stages of the study were conducted in 6 L column reactors. The reactors were operated under long period of sludge retention time of 20 days and in deficient dissolved oxygen of less than 2 mg/L in order to induce the sludge bulking phenomenon. After reaching its stable state, the activated sludge under the magnetic field exposure showed significant results as compared to without the exposure. The average aggregation and settling velocity for the magnetically exposed activated sludge were 89% and 0.59 m/hr as compared to 68% and 0.50 m/hr for the unexposed sludge. Such properties resulted in significant enhancement of sludge volume index at 23.7 mL/g for magnetically exposed activated sludge as compared to 72.2 mL/g for the unexposed sludge. This enhancement benefited the treatment performances whereby the average chemical oxygen demand, ammonia and total phosphorus removal were 87%, 88% and 72% under the magnetic field exposure as compared to 67%, 75% and 44%, respectively without the exposure. Magnetically exposed activated sludge also contained high content of tightly bound extra-cellular polymeric substances (95.6 mg/g VSS) compared to unexposed sludge (61.8 mg/g VSS). Finally, Next Generation Sequencing analysis indicated that magnetically exposed activated sludge showed less possibility of filamentous microorganisms presence compared to the unexposed activated sludge. Overall, analysis confirmed that magnetic field could enhance the settling property of activated sludge through improvement on its aggregation and bioflocculation capability. These imply that magnetic field is reliable for accelerating activated sludge settleability, hence enhancing performance efficiency of the treatment systems. The applied magnetic field was also proven to inhibit proliferation of filamentous microorganisms, thus has potential to inhibit occurrence of sludge bulking.